The Influence of Target Layout and Clicking Method on Picking Time and Dragging Performance Based on Eye-Control Technique - Wang, Lian; Wang, Dan; Zhou, Yingwei; Liu, Haixiao; Shi, Jinshou; Zhao, Yuting; Zhang, Chi; Niu, Jianwei (Frontiers in Psychology, 2020)
Eye-tracking has been a hot topic in human-computer interaction. Nevertheless, previous studies usu-ally adopted eye-tracking as information output rather than input. The eye-control technique can achieve convenient and rapid real-time operation through the movement of the eyes and reduce un-necessary manual operations. Because the layout determines the location orientation, organizational complexity, cognitive consistency, and predictive ability of the information display, the interface lay-out design affects the user's perception of information intensity, complexity, and logic. Moreover, the method of target clicking by eye-control techniques, which include blink and dwell, also depends on the application and user’s ability. The purpose of this study is to investigate the influence of target layout and target picking method on picking time and dragging performance based on eye-control technique. The results indicate that the target picking method, i.e., blink or dwell, had significant effects on the dragging time and dragging numbers. However, there was no significant effect of target layout on picking time and dragging performance (dragging time and numbers), which may be related to the setting of the experimental conditions (e.g., lighting level and screen resolution). Moreover, the target picking method and the target layout had no significant interaction effect on picking time and drag-ging performance. The findings are anticipated to provide helpful implications for future eye control technique design.